Initiatives of DIET Gangtok, Sikkim in Capacity Building of Teachers and Education Functionaries in Alignment with Learning Outcomes and NAS Report - Bhutia, Tshering Wangdi (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
National Council of Educational Research and Training (NCERT) has been periodically conducting National Achievement Surveys (NAS) for Class III, V, and VIII since 2001 with the objective of monitoring the improvement in children's learning levels and periodic assessment of the government education system as a whole. The NCF-2005 and the spirit of RTE Act-2009 have also emphasized on the assessment as it benefits the children, teacher and other stakeholders in fostering better performances leading to learning achievement of the children. The large-scale assessments like NAS may be used to identify the lacunas in the teaching-learning processes and also be used for improving the quality of teaching and learning processes through various interventions. DIETs, Gangtok- Sikkim on its own initiatives have tried to study the NAS reports of the state and the learning achievement levels.  This paper is an attempt to study the NAS report and Learning Outcome inclusive programmes and activities designed by DIET, Gangtok. The programmes include training and workshops (both pre-service and in-service), capacity building of elementary teachers, onsite support to schools on learning outcomes, mapping of innovative pedagogical practices and research. The paper is about how DIET, Gangtok has initiated the study on the inclusion of Learning outcomes in the programmes and activities of the institution. This process of initiation would benefit the children's learning achievement.  The paper also talks about the study on NAS report and its utilization in onsite support to schools on learning outcomes. The paper has two sections. The first section gives an insight into Sikkim schools NAS Report, 2017. The second section highlights the Planning and Designing of programmes and activities of DIET.